If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 6 = -20 Reorder the terms: 6 + 9x = -20 Solving 6 + 9x = -20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 9x = -20 + -6 Combine like terms: 6 + -6 = 0 0 + 9x = -20 + -6 9x = -20 + -6 Combine like terms: -20 + -6 = -26 9x = -26 Divide each side by '9'. x = -2.888888889 Simplifying x = -2.888888889
| 5p^2=-27p-10 | | (2x-1)(2x-1)=49 | | (4x+3)(4x+3)=7 | | 98x^2= | | (x+5)(x+5)=20 | | (x+3)(x+3)=44 | | (x+5)(x+5)=12 | | (5x+5)(5x+5)=100 | | 9x^2-12y+4=0 | | 4p+2=2p+10 | | x^2-5=20 | | (x+6)(x+6)=11 | | 14x+23=4x+174 | | 5277.356*85.36= | | (3x+3)(3x+3)=36 | | 3x+2y=50 | | 8-2(a+2)=a+7 | | 16t^2+36t-8=0 | | 12x^2+2x=24 | | 2x^2+5=2 | | a^2-5a=24 | | x^2-49=28 | | -1=3w-7 | | 227-4x=32x+19 | | 13-7x=213-42x | | 2(3n+3)=-10 | | -9=3x+9 | | 13*21= | | 6y^2-19y+15=0 | | 85-6x=10-7x | | x^3-x^2-10=0 | | 96-3x=5x+8 |